Sensitivity Analysis of Storm Duration for Development of Flood Map at Bertam Catchment, Cameron Highlands. - Zanial, W.N.C.W.; Malek, M.A.; Aziz, N.A.A. (International Journal of Engineering and Technology, 2018)
The current changes in climate have marked significant impacts in our daily weather. The changes have affected the trend, pattern and magnitude of rainfall-runoff as compared to the events commonly experienced. Flood is one of the effects of weather and climate change. Floods can be classified as one of the most devastating natural hazards and is a major concern to the country as it causes damages to human lives, environment, agriculture, land and structures. Therefore, effective flood planning and mitigation measures should be carried out in order to reduce the effects of flooding. Flood hazard map is one of the non-structural mitigation measures that can be used for planning purposes. Flood can be directly estimated or derived from frequency analysis when long duration of stream flow records is available. However, in the case of limited or no stream flow data available, design storm are generally used to estimate design flood. Downstream of Bertam Catchment is an ungauged river station where no flow records are available. Based on this limitation, in this study, design storm was used to design the flood map. Info Works RS was used to develop the flood model and sensitivity analysis of the design storm was performed. Results obtained in this study presented the comparison of flow between 100-years Annual Recurrence Interval (ARI) at various storm durations of 0.25hr, 0.5hr, 1hr, 3hrs, 6hrs, 12hrs, 1 day, 2days and 3 days. The maximum flow is found to be at 6hrs storm duration at 1103.418m3/s. Besides river flow, comparison of water level at 100-year ARI of various storm durations was also conducted. Results obtained from this study found that 24hrs storm duration will produce the highest water level at 1034.753m. By comparing the flow and water level, the result from river flow produces the maximum at 6hrs storm duration while the result of water level gives the maximum at 24hrs storm duration. Since, water level is preferable in producing flood hazard mapping at 2-D view, therefore, the storm duration is chosen based on results of sensitivity storm duration on water level conducted. Comparison is then conducted between 24-hrs storm duration at various ARIs. It can be concluded that 100-years ARI will lead to the maximum value of 1034.910mÂ  water level. Suitable storm duration and Annual Recurrence Interval (ARI) are to be determined in order to produce the best flood hazard map. In this study, it is found that 100-years ARI and 24hrs storm duration are the best combination, performed based on water level.